PENGETAHUAN IBU TENTANG TEHNIK POSISI MENYUSUI YANG BAIK DAN BENAR DI KELURAHAN PIJORKOLING KECAMATAN PADANGSIDIMPUAN TENGGARA TAHUN 2018 - EVA YUSNITA NASUTION (JURNAL ILMIAH KOHESI, 2020)
Breastfeeding techniques are certain measures in the delivery of breast MILK directly to infants for the importation ofBREASTFEEDING more effectively. Breastfeeding techniques are very influential for exclusive BREAST feeding.(Soetjiningsih, 2007). This research aims to determine the knowledge of mothers about the technique of good and correctbreastfeeding in Kelurahan Pijorkoling East Padangsidimpuan Sub-district year 2019, this research is descriptive, datacollection obtained through questionnaires, where samples of 40 respondents were researched based on age, education,occupation, parity and source of information. The Data is processed by editing, coding and tabulating and then analyzed andcollected in the table followed by discussing the results of the research with existing literature theory. The results of the studywere known that the majority of the respondents were less than 20 respondents (55%), the majority of the respondents wereless than 20-35 years old as many as 19 respondents (47.5%), the majority of knowledgeable respondents with no educationgraduated from elementary school and graduated with as many as 7 respondents (17.5%), The majority of knowledgeablerespondents worked as a self-employed 10 respondents (25%), and the majority of the knowledgeable respondents wereless than 8 respondents (20%). From the research results obtained respondents categorized less knowledgeable. Toimprove the knowledge of mothers on the techniques of breastfeeding positions that are good and correct in need ofcooperation between health workers with mothers to realize the baby can get breast milk in a good and correct way.